PEMERTAHANAN BAHASA SASAK PADA KELUARGA BANGSAWAN LOMBOK (Studi Etnografi di Kabupaten Lombok Timur) - Mugni Sn (Jurnalistrendi : Jurnal Linguistik, Sastra dan Pendidikan, 2016)
The focus of this study is Sasak language maintenance at Lombok noble  family with subfokus, the domains of the Sasak language (base alus) use at  the noble family, difficulties in maintaining Sasak language (base alus) at the noble family, and efforts noble family  in maintaining Sasak language (base alus) at East Lombok regency.  Sources of data in this study is noble families who are living in  and outside pedalaman at the  Suradadi village,  Padamara, and Rakam. Of the entire population is in accordance with criteria established by the determination of informan 28 researchers elected noble family. They stay in the interior, beyond pedalam in the  village and outdoor. Methods of data collection in this research is observation, interview, documentation, questionnaires, and tests (translation). While the methods of data analysis using Spradley approach, by focusing on domain analysis, taxonomy, and the discovery of cultural themes. Data  analysis is  found noble families maentenance Sasak language (base alus) by using the language in communicating with family and others who are newly recognized. Language Sasak (base alus) are also used in electronic mass media programs (radio and local television are cared for by nobles). Domain of language use is a Sasak family, friendship, and religious. Sasak language is not used in the realm of work and schooling (education). Constraints in Sasak language maintenance is the claim that Sasak language  (base alus) is a noble language,  many noble families who live in the expansion, the Sasak language (base alus) does not  economic value, less attention from Adat Sasak Assembly on cultural activities that require the use of base alus, and the government has not given attention in Sasak language (base alus). As for the cultural theme of this research are  terinventaris nobility Sasak language (base alus) in communicating with older nobility in terms of age and the trooper post in the genealogy;  nobility families are use Sasak language (base alus) when meeting new people; Sasak language (base alus) did not learn from the priend of noble familiy, and for maintenaning Sasak lunguage need suport informal education and all Sasak sociaty.